DEVELOPMENT OF A QR-CODE INTEGRATED WEB-MOBILE FLORA EDUCATION INFORMATION SYSTEM FOR EDUCATIONAL TOURISM IN SUMBER REJO TOURISM VILLAGE - Wahyu Sulistianing Budi; Miftahurrofi Asidqi; Tuti Puspitasari (YHMM PUBLISHING, 2025)
The rapid development of digital technology has encouraged the implementation of information systems in educational tourism to improve visitor learning experiences. This study aims to develop a QR-Code integrated web-mobile flora education information system for Sumberrejo Tourism Village. The system was designed to provide visitors with easy access to information about flora collections, including plant names, classifications, benefits, and descriptions through QR-Code scanning using smartphones or computers. The research employed a Waterfall development method consisting of requirement analysis, system design, coding, testing, and maintenance stages. Data collection techniques included observation, interviews, and literature studies. System testing was conducted using the Black Box Testing method involving 64 community members and 32 school-age children. The results showed that the system achieved an average success rate of 92.7%, indicating that the application effectively supports educational tourism, improves flora literacy, and enhances visitor interaction through digital technology integration.